Armband activity monitor data do not correlate with reported pain scores in patients receiving vertebroplasty. (28th July 2016) - Peacock, Justin G; Vine, Roanna L; McDonald, Jennifer S; Novotny, Paul J; Kallmes, David F
Abstract : Background: Prior research on the efficacy of vertebroplasty has focused primarily on subjective, patient-reported outcomes. Objective: To apply an armband activity monitor (SenseWear by BodyMedia Inc, USA) to patients presenting for consideration for vertebroplasty and to determine the correlation between patient-reported outcomes and quantitative activity metrics at baseline and 30 days after presentation. Materials and methods: Nineteen patients were enrolled (15 receiving vertebroplasty, 4 not receiving vertebroplasty). Patients reported their average pain over the past 24 hours and completed the Roland–Morris disability questionnaire at baseline and 30 days. Patients wore the SenseWear Armband activity monitor for a median of 4 days at baseline and at the 30-day time period to assess steps, metabolic equivalents expended, sedentary activity time, moderate activity time, sleep efficiency, and total sleep time. Pain and disability scores were correlated with activity monitor metrics using linear regression analysis. Results: Changes in reported average pain in the past 24 hours and disability scores were not significantly different between vertebroplasty and non-vertebroplasty groups (p>0.05). Changes in activity monitor data were not significantly different between the vertebroplasty and non-vertebroplasty groups (p>0.05). None of the correlations between the reported pain or disability scores and the activity monitor data were significant. Conclusions: Activity monitors can be used to objectively record changes in activity following vertebroplasty procedures. Patient-reported pain or disability scores do not correlate with activity monitor-measured activity or sleep metrics.